Implicit Learning of Viewpoint-Independent Spatial Layouts - tsuchiai, taiga; matsumiya, kzumichi; kuriki, ichiro; Shioiri, Satoshi (Frontiers in Psychology, 2012)
We usually perceive things in our surroundings as unchanged despite viewpoint changes caused by self-motion. The visual system therefore must have a function to process objects independently of viewpoint. In this study, we examined whether viewpoint-independent spatial layout can be obtained implicitly. For this purpose, we used a contextual cueing effect, a learning effect of spatial layout in visual search displays known to be an implicit effect. We compared the transfer of the contextual cueing effect between cases with and without self-motion by using visual search displays for 3D objects, which changed according to the participant’s assumed location for viewing the stimuli. The contextual cueing effect was obtained with self-motion but disappeared when the display changed without self-motion. This indicates that there is an implicit learning effect in spatial coordinates and suggests that the spatial representation of object layouts or scenes can be obtained and updated implicitly. We also showed that binocular disparity play an important role in the layout representations.